Language distinctions in Russophone groups of the Polish segment of Facebook - Serebriansky, Yuriy (Przegląd Wschodnioeuropejski, 2024)
The article examines the distinctions of the Russian language used by Ukrainians living in Poland. The study is based on the analysis of Facebook groups in the Polish segment, where both private and commercial messages are posted. The article presents the findings of an analysis of language insertions from the Polish language and other linguistic features of messages in online groups, specifically focusing on the use of toponyms and elements of speech etiquette of the Russian language. Additionally, data on the dynamics of changes in the number of group members and the frequency of Russian and Ukrainian language use in these groups from January to September 2022 are presented.